Steamers QUEEN and GEO. W. ELDER in the harbor at Skagway, Alaska, 1897. - La Roche, Frank (1897)
Caption on image: ""Steamers Queen and George W. Elder at Skagway. c. 1897"" ""Steamers Queen and George W. Elder at Skaguay. The steamer Queen which is a speedy boat and affords excellent accommodations, has carried thousands of tourists to Alaska during the past excursion seasons. The George W. Elder which is not so commodious a boat, sails direct for Portland. Both vessels had just arrived at the head of steam navigation on Lynn Canal laden with crowds of gold-seekers and tons upon tons of supplies. Two streams follow a natural outlet to the sea on each side of the high point of land to the right - on one side the Skaguay River, on the other side the Dyea. It is sometimes difficult to decide which route to take. Both Dyea and Skaguay trails have advantages which appeal differently to many travelers."" (Frank La Roche, En Route to the Klondike, 1898) To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number